Silicon polymer material and preparation method thereof
The silicon polymer material prepared by synergistically using short-chain aliphatic silicon monomers, long-chain polysiloxane monomers and aromatic silicon monomers has solved the problems of high moisture content and low oxygen permeability of existing soft contact lens materials, and achieved low water content, high oxygen permeability and good anti-adsorption performance, which is suitable for the preparation of low-water soft contact lenses.
Patent Information
- Application Number
- CN202411808621.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Existing soft contact lens materials have problems such as high moisture content that leads to worsening of dry eyes, difficulty in reaching high oxygen permeability, and bacterial reproduction and protein and lipid adsorption.
Low-water, highly oxygen permeable silicon polymer materials prepared by synergistically acting short-chain aliphatic silicon monomers, long-chain polysiloxane monomers and aromatic silicon monomers, combined with molding and surface hydrophilic polymer grafting technology, materials suitable for ophthalmic lenses are prepared.
It achieves mechanical properties such as low water content, high oxygen permeability, soft and improved toughness, and has unexpected anti-protein and lipid adsorption properties, reducing the risk of corneal edema and dry eye.
Smart Images

Figure BDA0005179955830000041 
Figure BDA0005179955830000042 
Figure BDA0005179955830000051
Abstract
Description
Technical Field
[0001] The present invention relates to a silicon polymer material. Furthermore, the present invention introduces a lens material with high oxygen permeability, low water content and softness and a preparation method thereof, in particular, an ophthalmic lens material suitable for preparation by compression molding. Background Art
[0002] Corneal oxygen metabolism is a key link in the eye's sugar metabolism, energy metabolism, electrolyte metabolism, and water balance metabolism. The cornea's oxygen intake is crucial. The oxygen required for corneal glucose metabolism is mainly provided by the tear film. When the eyes are open, the tear film is in direct contact with the atmosphere, and the oxygen in the atmosphere is directly provided to the cornea through the tear film. When wearing contact lenses, the channel for direct oxygen supply from the cornea to the outside world is blocked. Therefore, the contact lens material must have sufficient oxygen permeability to meet the cornea's oxygen metabolism function and ensure the wearer's cornea safety.
[0003] Contact lenses can be divided into hydrogel contact lenses and non-hydrogel contact lenses according to the water content of the lens material. Hydrogel contact lenses are generally soft contact lenses, which have a water content of ≥10% after equilibration in a standard saline solution, including hydrogel contact lenses and silicone hydrogel contact lenses. Non-hydrogel contact lenses are currently mainly hard contact lenses with a water content of less than 10% (such as RGP lenses / scleral lenses / orthokeratology lenses, etc.), but soft, low-water-content, high-oxygen-permeable contact lenses are rarely available.
[0004] Currently, the soft contact lenses on the market are generally hydrogel (silicon-containing hydrogel) contact lenses with a water content of 25% to 80%. Some wearers experience a stronger sense of dryness and discomfort than the naked eye, and even worse dry eye symptoms. This may be caused by the lens absorbing water from tears and increasing tear evaporation after wearing the lens. In addition, due to its high water content, it is difficult for hydrogel contact lenses to achieve a high oxygen permeability and cannot meet the requirements of long-term continuous wear; silicone hydrogel contact lenses increase the oxygen permeability of the lens by adding silicon-containing components to the lens material. Due to the need to take into account the compatibility of lipophilic silicone components and hydrophilic components, it is difficult to take into account both the oxygen permeability and softness and comfort of silicone hydrogel lenses. In addition, hydrogel (silicon-containing hydrogel) material water-containing contact lenses are easily contaminated by tear components, and because their material contains a large amount of water, there is also a risk of bacterial growth.
[0005] The non-hydrogel contact lens material substrate contains almost no hydrophilic components and is not restricted by the compatibility of hydrophobic silicone monomers and hydrophilic monomers. The material has good transparency, excellent optical properties of the lens, and higher visual clarity. Since the proportion of silicone monomers in the material is not limited, the oxygen permeability coefficient of the lens can be as high as 300 or more, ensuring the safety of long-term continuous wear.
[0006] Existing non-hydrogel contact lenses are generally made of hard fluorosilicone acrylate. Although they have the advantages of low water content and high oxygen permeability, the hardness of the lens substrate reduces wearing comfort and may cause corneal injury when the fitting parameters are not matched or the lens is damaged. Non-hydrogel soft contact lenses are mainly made of traditional silicone rubber and have gradually faded out of the market. The main reasons are: (1) The silicon monomer composition of traditional silicone rubber is simple and cannot have mechanical properties such as high oxygen permeability, softness and toughness; (2) Traditional silicone rubber soft contact lenses cannot be widely used due to the high surface viscosity, which makes it easy to adhere to the cornea (fixation) or the silicone rubber substrate material cannot be firmly combined with the hydrophilic coating.
[0007] The art hopes to obtain a material with low oxygen permeability, flexibility and strength, and suitable for surface coating. The inventors of the present invention utilize the advantages of high oxygen permeability and low water content of non-hydrogels to solve the problems of the prior art and provide a silicone polymer material with low water content, high oxygen permeability, moderate toughness, and suitable for hydrophilic coating, which is particularly suitable for use in ophthalmic lenses and has unexpected resistance to protein and lipid adsorption, and is particularly suitable for use in the preparation of low-water soft contact lenses for correcting human eye refractive errors. Summary of the invention
[0008] The present invention solves the problems of water evaporation, dry eye, bacterial growth, protein and lipid adsorption, etc. in soft contact lenses containing silicone hydrogel (generally referred to as hydrogel) in the prior art, and takes into account mechanical properties such as low water content and high oxygen permeability, excellent softness and improved toughness, and is suitable for surface coating of contact lens materials and contact lenses prepared therefrom.
[0009] The inventors unexpectedly discovered that the silicon polymer material of the present invention solves the problems existing in the above-mentioned prior art. The silicon polymer material is prepared by the synergistic effect between the silicon monomers selected by the present invention. The obtained silicon polymer material of the present invention can take into account low water content, high oxygen permeability, softness and improved mechanical properties such as toughness, and has unexpected resistance to protein and lipid adsorption. The material is suitable for surface coating and the contact lenses prepared from it are comfortable, and long-term wearing can reduce the risk of corneal edema and dry eyes.
[0010] The silicon polymer material of the present invention is a silicon polymer material prepared by polymerization through the synergistic effect of the following silicon monomers, wherein:
[0011] The first silicon monomer is selected from acrylate or acrylamide short-chain aliphatic silicon monomers;
[0012] The second silicon monomer is selected from a single-terminated or double-terminated long-chain polysiloxane monomer of acryloxy or acrylamide type;
[0013] The third silicon monomer is selected from styrene-based aromatic silicon monomers.
[0014] The present invention also relates to medical devices comprising the silicone polymer material of the present invention, such as contact lenses, colored contact lenses, intraocular lenses, artificial corneas, intracorneal rings, intracorneal lenses, intraocular fillings, etc.
[0015] The present invention also relates to a method for preparing a silicon polymer material, comprising:
[0016] - preparing a substrate by compression molding a mixture of monomers, a crosslinking agent and / or an auxiliary agent used in the silicon polymer material of the present invention;
[0017] - Optionally, the substrate is immersed in a solution containing an oxidant and a hydrophilic polymer and fixed by covalent cross-linking.
[0018] Silicon Monomer
[0019] In the present invention, the first silicon monomer (Si1) and the second silicon monomer (Si2) have similar acrylate and / or acrylamide structures. By controlling the usage ratio of the two, the first silicon monomer plays a solubilizing role on the second silicon monomer, thereby increasing the proportion of the second silicon monomer, i.e., the long-chain polysiloxane monomer, in the polymer material, which is beneficial to improving the flexibility of the medical device material without affecting the optical transparency of the material; the third silicon monomer (Si3) is selected from styrene aromatic silicon monomers, has a higher free volume, and the rigid styrene conjugated structure is beneficial to improving the mechanical strength of the material. Through its synergistic effect with the second silicon monomer, the long-chain polysiloxane is filled in the gaps of the third silicon monomer, making the material denser and making the content of silicon atoms that transmit oxygen higher, thereby improving the mechanical strength of the material such as toughness while also improving the oxygen permeability of the material.
[0020] The synergistic relationship between the three silicon monomers, such as Figure 1 As shown, Figure 1 For example, Figure 1 The ratio between silicon monomers is not strictly shown.
[0021] As described in the present invention, the synergistic effect of the three silicon monomers makes the silicon polymer material described in the present invention a silicon polymer material with low water content, high oxygen permeability, moderate toughness and suitability for hydrophilic coating, which is particularly suitable for use as a material for ophthalmic lenses and has unexpected resistance to protein and lipid adsorption, and is particularly suitable for the preparation of low-water soft contact lenses for correcting refractive errors of the human eye.
[0022] The first silicon monomer is selected from short-chain aliphatic silicon monomers. According to a specific embodiment of the present invention, the first silicon monomer is specifically selected from at least one of acrylate or acrylamide silicon monomers, for example, the molecular structure is:
[0023]
[0024] in:
[0025] R1=H or C 1-6 Alkyl, preferably H or CH3;
[0026] n=1-20, preferably 1-6, especially 2-5, even 3 or 4;
[0027] R2, R3 and R4, which may be the same or different, are selected from H, CH3, OCH3, OCH2CH3, OSi(CH3)3, CH(OCH2CH3)2 and C(OCH2CH3)3.
[0028] According to a specific embodiment of the present invention, the first silicon monomer can be selected from: 3-(trimethoxysilyl)propyl acrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-[dimethoxy(methyl)silyl]propyl methacrylate, 3-[diethoxy(methyl)silyl]propyl methacrylate, 3-(methoxydimethylsilyl)propyl acrylate, 3-(triethoxysilyl)propyl methacrylate, 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, acrylamidopropyl trimethoxysilane, (3-methacrylamidopropyl)triethoxysilane, 3-acrylamidopropyl tri(trimethylsiloxy)silane, (3-methacrylamidopropyl)tri(trimethylsiloxy)silane, and the like.
[0029] The second silicon monomer is a long-chain polysiloxane monomer. According to a specific embodiment of the present invention, it is preferably selected from one or more polydimethylsiloxanes with single or double end capping of acryloyloxy or methacryloyloxy or acrylamide or methacrylamide, and its molecular weight is above 1000, preferably 1500 to 50000, more preferably 1500 to 20000, or 3000 to 15000, or even 5000 to 10000. For example, the molecular structure is:
[0030]
[0031]
[0032] in:
[0033] W is X-(CH2)pY(CH2)q;
[0034] R′1=H or C 1-6 Alkyl, preferably H or CH3;
[0035] p=1-20, preferably 1-6, especially 2-5, even 3 or 4;
[0036] q=1-20, preferably 1-6, especially 2-5, even 3 or 4;
[0037] m=1-100, preferably 15-60, especially 20-40;
[0038] X is selected from O, S or NH;
[0039] Y is absent or selected from O or S or NH or NHCOO(CH2)tO or NHCOO(CH2)tS or NHCOO(CH2)tNH, where t=1-20, preferably 1-6, especially 2-5, even 3 or 4;
[0040] R'2 and R'3, the same or different, are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, either straight chain or C 6-20 One or more of heteroarylalkyl or OCH3 or OCH2CH3 or OSi(CH3)3 or CH(OCH2CH3)2 or C(OCH2CH3)3;
[0041] R′4 is selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl or C 6-20 Arylalkyl, either straight chain or C 6-20 Heteroarylalkyl; preferably C1-4 alkyl.
[0042] The third silicon monomer is an aromatic silicon monomer. According to a specific embodiment of the present invention, it is preferably selected from a styrene-containing silicon monomer, for example, the molecular structure is:
[0043]
[0044] R″1=H or C1-6 alkyl, preferably H or CH3;
[0045] R"5 and R"6 are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl, or one or more of Si(CH3)3;
[0046] X' is absent or is selected from O or S or a linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, or C 6-20 heteroarylalkyl; or C 3-20 heterocyclylalkyl;
[0047] R″2, R″3 and R″4 are the same or different and are selected from one or more of CH3, OSi(CH3)3, OSiCH2CH2Si(CH3)3 and SiCH2CH2Si(CH3)3.
[0048] In addition to the structures listed in the above formula, the aromatic silicon monomers in the present invention may also include silicon monomers containing an "aryl" group in the structure, wherein the "aryl" group may refer to a phenyl group (i.e., a monocyclic aromatic group) or a bicyclic system containing at least one benzene ring or an aromatic bicyclic ring containing only carbon atoms in the aromatic bicyclic system. The bicyclic aromatic group may be selected from azulenyl, naphthyl, or a phenyl group fused to a monocyclic cycloalkyl, a monocyclic cycloalkenyl, or a monocyclic heterocyclic group, wherein in particular, the bicyclic aromatic group is connected to the parent molecular part through any carbon atom contained in the phenyl part of the bicyclic system or any carbon atom of the naphthyl or azulenyl ring, wherein in particular, the fused monocyclic cycloalkyl or monocyclic heterocyclic group part of the bicyclic aromatic group is optionally substituted with one or two oxo and / or thia groups. Representative examples of bicyclic aryl groups include, but are not limited to, azulenyl, naphthyl, indan-1-yl, indan-2-yl, indan-3-yl, indan-4-yl, 2,3-dihydroindol-4-yl, and the like.
[0049] In the present invention, the weight ratio of the first silicon monomer: the second silicon monomer: the third silicon monomer is (40-55): (40-60): (0.1-5), or even (40-50): (45-59): (0.2-4), in particular (40-48): (50-58): (0.3-3), and preferably (40-45): (52-58): (0.5-2.5).
[0050] Crosslinking agent
[0051] In the present invention, according to a specific embodiment of the present invention, the crosslinking agent can be selected from one or more of ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tri(ethylene glycol) divinyl ether, tetraethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, glycerol dimethacrylate, glycerol trimethacrylate, propylene glycol dimethacrylate, 1-(acryloyloxy)-3-(methacryloyloxy)-2-propanol, polyethylene glycol dimethacrylate (wherein the polyethylene glycol preferably has a molecular weight of up to about 5000), vinyl methacrylate, ethylenediamine dimethylacrylamide, and triallyl isocyanurate.
[0052] According to one embodiment of the present invention, the amount of the crosslinking agent is 0.02 to 5%, or 0.05 to 4%, in particular 0.1 to 3%, or even 0.15 to 1%, based on the total mass (100%) of the components of the present invention.
[0053] Additives
[0054] In the process of preparing the silicon polymer material of the present invention, an initiator may need to be used, and a photoinitiator or a thermal initiator may be used.
[0055] The photoinitiator can be selected from, but not limited to, benzoin methyl ether, diethoxyacetophenone, benzoylphosphine oxide initiator, ethyl dimethylaminobenzoate, 2-isopropylthioxanthone, 1-hydroxycyclohexyl phenyl ketone, Darocure series initiators or Irgacure series initiators. The initiator is preferably Irgacure-819 or Darocure-1173.
[0056] The thermal initiator includes but is not limited to an azo or peroxide initiator, such as azobisisoheptanenitrile (ADVN), azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), Trigonox series initiators or Perkdox series initiators.
[0057] According to one embodiment of the present invention, the amount of the initiator is 0.02 to 5%, or 0.05 to 4%, in particular 0.1 to 3%, or even 0.2 to 2%, based on the total mass (100%) of the components of the present invention.
[0058] In the silicon polymer material of the present invention, an ultraviolet light absorber, a blue light absorber, and / or a dye or pigment capable of imparting different colors to the material may be added.
[0059] The ultraviolet light absorber includes but is not limited to: a compound selected from the group having an efficient absorption function for ultraviolet light with a wavelength range below 380 nm. Preferably, the benzophenone compounds and / or benzotriazole compounds are highly safe. More preferably, the benzophenone compounds and / or benzotriazole compounds contain a polymerizable group, and the polymerizable group is selected from the group consisting of vinyl, allyl, butenyl, ethynyl, acryloyloxy, methacryloyloxy, acrylamide, methacrylamide, and vinyl ether.
[0060] The blue light absorber includes but is not limited to: a compound selected from compounds having a selective filtering function for blue light within a wavelength range of 400 to 500 nm.
[0061] In silicon polymer material of the present invention, pigment and / or dye can be added, it is selected from but not limited to the compound that can be used for contact lenses of U.S. FDA approval.Specifically, synthetic pigment and / or dye or natural pigment and / or dye, for example copper phthalocyanine, reactive blue 4, reactive blue 19, reactive blue 21, reactive blue 246, reactive blue 247, reactive yellow 15, reactive orange 78, reactive red 11, titanium dioxide, reactive black 5, D&C green 4, D&C blue 6, D&C green 6, D&C yellow 10, fluorescein sodium, brilliant blue, eosin, carmine, lemon yellow, amaranth, erythrosine, new red, indigo, acid red, lycopene.Especially, described natural pigment and / or dye comprise natural pigment, for example be selected from anthocyanin, anthocyanin, wolfberry pigment, grape skin pigment, gardenia blue pigment, red rice red pigment, red bean red pigment, betalain red pigment.According to a specific embodiment of the present invention, the yellow dye compound containing azo group in the molecular structural formula can be used.
[0062] According to one embodiment of the present invention, pigment and / or dye compounds containing polymerizable groups can be used, and the polymerizable groups are selected from vinyl, allyl, butenyl, ethynyl, acryloxy, methacryloyloxy, acrylamide, methacrylamide, vinyl ether.
[0063] According to a specific embodiment of the present invention, the content of the synthetic pigment and / or dye, or natural pigment and / or dye is 0 to 10% by mass, or 0.01 to 6%, in particular 0.2 to 4%, or even 0.5 to 2%.
[0064] According to a specific embodiment of the present invention, based on the total mass (100%) of the components of the present invention, the amount of ultraviolet absorber and blue light absorber is 0 to 3%, or 0.01 to 2%, especially 0.02 to 1%, or even 0.05 to 0.5%.
[0065] In the process of preparing the silicon polymer material of the present invention, a diluent such as a solvent and / or a hydrophilic polymer may be added. When the material contains a diluent, the reactive components are usually mixed in the diluent to form a reaction mixture. Applicable diluents may include alcohols having 2 to 20 carbon atoms, carboxylic acids having 8 to 20 carbon atoms, poly-N,N-dimethylacrylamide, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, amides derived from primary amines having 10 to 20 carbon atoms and carboxylic acids having 8 to 20 carbon atoms, and the like. Specifically, the diluent may include one or more of 1-ethoxy-2-propanol, diisopropylaminoethanol, isopropanol, 3,7-dimethyl-3-octanol, 1-decanol, 1-dodecanol, 1-octanol, 1-pentanol, 2-pentanol, 1-hexanol, 2-hexanol, 2-octanol, 3-methyl-3-pentanol, tert-pentanol, tert-butanol, 2-butanol, 1-butanol, 2-methyl-2-pentanol, 2-propanol, 1-propanol, ethanol, 2-ethyl-1-butanol, 1-tert-butoxy-2-propanol, 3,3-dimethyl-2-butanol, tert-butoxyethanol, 2-octyl-1-dodecanol, decanoic acid, octanoic acid, dodecanoic acid, 2-(diisopropylamino)ethanol, poly N,N-dimethylacrylamide, polyvinyl alcohol, polyethylene glycol, and polyvinyl pyrrolidone.
[0066] According to one embodiment of the present invention, the amount of the diluent is 0 to 15%, or 0.5 to 12%, in particular 1 to 10%, or even 2 to 8%, based on the total mass (100%) of the components of the present invention.
[0067] The present invention also relates to a method for preparing the silicon polymer material of the present invention, comprising the following steps:
[0068] -(1) mixing the required components, such as the first silicon monomer, the second silicon monomer, the third silicon monomer, the crosslinking agent, the initiator or optionally the dye and / or pigment, the light absorber, and optionally removing bubbles;
[0069] - (2) polymerizing the mixture, optionally placing it in a mold for polymerization, preferably by thermal polymerization and / or photopolymerization; then, optionally, subjecting the obtained polymer to subsequent treatment such as molding.
[0070] The present invention also relates to a method for preparing a medical device such as a contact lens obtained from the silicon polymer material of the present invention, comprising the following steps:
[0071] -(1) mixing the required components, such as the first silicon monomer, the second silicon monomer, the third silicon monomer, the crosslinking agent, the initiator or optionally the dye and / or pigment, the light absorber, and optionally removing bubbles;
[0072] - (2) polymerizing the mixture, optionally placing it into a mold such as a mold for a medical device (e.g., a contact lens), preferably by thermal polymerization and / or photopolymerization;
[0073] -(3) optionally, extracting with an organic solvent;
[0074] - (4) optionally, a hydration step, an equilibration step with a balanced saline solution, and a sterilization step;
[0075] -(5) Molding to prepare a substrate.
[0076] According to a specific embodiment of the present invention, the step of surface grafting a hydrophilic polymer is also included, including: immersing the substrate of the medical device (such as a contact lens) in a solution containing the hydrophilic polymer and an oxidant, and then performing a chemical reaction to obtain the medical device. Since the first silicon monomer and the second silicon monomer in the silicon polymer material of the present invention contain acrylate and acrylamide structures, the hydrophilic polymer is easier to spread on the surface of the lens substrate, and then covalently grafted on the surface under the action of the oxidant to form a uniform and stable hydrophilic coating.
[0077] Preferably, the hydrophilic polymer is selected from one or more of the following: a hydrophilic polymer containing a cyclic amide or cyclic imine structure in the main chain, poly N,N-dimethylacrylamide, polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyethylene oxide, poly 2-ethyl-oxazoline, a polymer containing a phosphorylcholine vinyl monomer, and one or more polysaccharides, preferably polyvinyl pyrrolidone, poly N-vinyl-2-piperidone, poly N-vinyl-2-caprolactam, poly N-vinyl-3-methyl-2-caprolactam, poly N-vinyl-3-methyl-2-piperidone, poly N-vinyl-4-methyl-2-piperidone, poly N-vinyl-4-methyl-2-caprolactam, poly N-vinyl-3-ethyl-2-pyrrolidone, poly N-vinyl-4,5-dimethyl-2-pyrrolidone, and polyvinyl imidazole.
[0078] According to a specific embodiment of the present invention, the oxidant can be selected from one or more of peroxides or persulfides, preferably one or more of hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate.
[0079] The present invention also relates to a medical device, preferably, a contact lens, a colored contact lens, an intraocular lens, an intraocular lens, an artificial cornea, an intracorneal ring, an intracorneal lens, a drug release carrier, an intraocular filler, a medical device lens or a medical treatment device such as a device for treating ophthalmic diseases, preferably a low-water soft contact lens, which may or may not be equipped with electronic devices. Contact lenses equipped with electronic devices such as sensors are based on measuring changes in resistance, inductance and capacitance generated in response to pressure-induced strain. Electronic sensing methods are sensitive to the hydration level of contact lenses. Therefore, electronic sensors for contact lenses are generally made of silicone rubber (which has a very low water content).
[0080] Specifically, the present invention relates to the following embodiments:
[0081] Item 1. A silicon polymer material, which is polymerized from silicon monomers, wherein the silicon monomers include at least a first silicon monomer, a second silicon monomer, and a third silicon monomer,
[0082] The first silicon monomer is selected from short-chain aliphatic silicon monomers, the second silicon monomer is selected from long-chain polysiloxane monomers, and the third silicon monomer is selected from aromatic silicon monomers.
[0083] The weight ratio of the first silicon monomer: the second silicon monomer: the third silicon monomer is (30-70): (20-60): (0.05-10).
[0084] Item 2. The silicon polymer material according to Item 1, wherein the first silicon monomer is selected from at least one of acrylate or acrylamide silicon monomers, such as a short-chain aliphatic silicon monomer of the following formula:
[0085]
[0086] R1=H or C 1-6 Alkyl, preferably H or CH3;
[0087] n = 1-20, preferably 1-6, even 2-5;
[0088] R2, R3 and R4 may be the same or different and are selected from one or more of H, CH3, OCH3, OCH2CH3, OSi(CH3)3, CH(OCH2CH3)2 and C(OCH2CH3)3.
[0089] Item 3. A silicon polymer material according to any of the preceding items, wherein the first silicon monomer is selected from: 3-(trimethoxysilyl)propyl acrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-[dimethoxy(methyl)silyl]propyl methacrylate, 3-[diethoxy(methyl)silyl]propyl methacrylate, 3-(methoxydimethylsilyl)propyl acrylate, 3-(triethoxysilyl)propyl methacrylate, 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, acrylamidopropyltrimethoxysilane, (3-methacrylamidopropyl)triethoxysilane, 3-acrylamidopropyltri(trimethylsiloxy)silane, (3-methacrylamidopropyl)tri(trimethylsiloxy)silane.
[0090] Item 4. A silicon polymer material according to any one of the preceding items, wherein the second silicon monomer is selected from one or more of acryloxy or methacryloxy or acrylamide or methacrylamide mono-terminated or di-terminated polydimethylsiloxanes, such as a long-chain polysiloxane monomer of the following formula:
[0091]
[0092] R′1=H or C 1-6 Alkyl, preferably H or CH3;
[0093] p = 1-20, preferably 1-6, or even 2-5;
[0094] q = 1-20, preferably 1-6, or even 2-5;
[0095] m=1-100, preferably 15-60;
[0096] X is O, S or NH;
[0097] Y is absent or selected from: O, S, NH, NHCOO(CH2)To, NHCOO(CH2)tS or NHCOO(CH2)tNH, where t=1-20, preferably 1-10, even 2-6, especially 3-5;
[0098] R'2 and R'3, the same or different, are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, either straight chain or C 6-20 One or more of heteroarylalkyl or OCH3 or OCH2CH3 or OSi(CH3)3 or CH(OCH2CH3)2 or C(OCH2CH3)3;
[0099] R′4 is H or a linear or branched, saturated or unsaturated C 1-20 Alkyl or C 6-20Arylalkyl, either straight chain or C 6-20 Heteroarylalkyl; preferably C1-4 alkyl; W is X-(CH2)pY(CH2)q.
[0100] Item 5. A silicon polymer material according to any of the preceding items, wherein the second silicon monomer is selected from: bis-3-(meth)acryloxypropyl polydimethylsiloxane, α-3-(meth)acryloxypropyl-w-n-butyl-polydimethylsiloxane, bis-4-(meth)acryloxybutyl polydimethylsiloxane, α-4-(meth)acryloxybutyl-w-n-butyl-polydimethylsiloxane, bis-3-(meth)acryloxyethoxypropyl polydimethylsiloxane, α-3-(meth)acryloxyethoxypropyl-w-n-butyl-polydimethylsiloxane Oxane, bis-4-(meth)acryloxyethoxybutyl polydimethylsiloxane, α-4-(meth)acryloxyethoxybutyl-w-n-butyl-polydimethylsiloxane, bis-3-(meth)acryloxycarbamate propyl polydimethylsiloxane, α-3-(meth)acryloxycarbamate propyl-w-n-butyl-polydimethylsiloxane, bis-4-(meth)acryloxycarbamate butyl polydimethylsiloxane, α-4-(meth)acryloxycarbamate butyl-w-n-butyl-polydimethylsiloxane.
[0101] Item 6. The silicon polymer material according to any one of the preceding items, wherein the second silicon monomer has a molecular weight of greater than 1,000, preferably from 1,500 to 50,000, more preferably from 5,000 to 30,000, and especially from 8,000 to 20,000.
[0102] Item 7. The silicon polymer material according to any of the preceding items, wherein the third silicon monomer is selected from styryl-containing silicon monomers, such as styryl-containing silicon monomers of the following formula (E):
[0103]
[0104] R″1=H or C1-6 alkyl, preferably H or CH3;
[0105] R"5 and R"6, identical or different, are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl, or one or more of Si(CH3)3;
[0106] X' is absent or is selected from O or S or a linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, or C 6-20 heteroarylalkyl; or C 3-20 heterocyclylalkyl;
[0107] R″2, R″3 and R″4, which are the same or different, are selected from one or more of CH3, OSi(CH3)3, OSiCH2CH2Si(CH3)3 and SiCH2CH2Si(CH3)3.
[0108] Item 8. A silicon polymer material according to any of the preceding items, wherein the third silicon monomer is selected from: 4-[tris(trimethylsiloxy)silyl]styrene, 4-[tris(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[tris(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[tris(trimethylsiloxy)silyl]styrene, 4-[methoxybis(trimethylsiloxy)silyl]styrene, 4-[methoxybis(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[methoxybis(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[methoxybis(trimethylsiloxy)silyl]styrene, 4-[dimethoxy(trimethylsiloxy)silyl]styrene, 4-[dimethoxy(trimethylsiloxy)silyl]methylstyrene Ethylene, 3-methyl-4-[dimethoxy(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[dimethoxy(trimethylsiloxy)silyl]styrene, 4-[ethoxybis(trimethylsiloxy)silyl]styrene, 4-[ethoxybis(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[ethoxybis(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[ethoxybis(trimethylsiloxy)silyl]styrene, 4-[diethoxy(trimethylsiloxy)silyl]styrene, 4-[diethoxy(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[diethoxy(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[diethoxy(trimethylsiloxy)silyl]styrene.
[0109] Item 9. A silicon polymer material according to any of the preceding items, wherein the crosslinker is selected from one or more of ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tri(ethylene glycol) divinyl ether, tetraethylene glycol dimethacrylate, trimethylpropane trimethacrylate, trimethylolpropane trimethacrylate, glycerol dimethacrylate, glycerol trimethacrylate, propylene glycol dimethacrylate, 1-(acryloyloxy)-3-(methacryloyloxy)-2-propanol, polyethylene glycol dimethacrylate (wherein the polyethylene glycol preferably has a molecular weight of up to about 5000), vinyl methacrylate, ethylenediamine dimethylacrylamide, and triallyl isocyanurate.
[0110] Item 10. A silicon polymer material according to any of the preceding items, wherein the weight ratio of the first silicon monomer: the second silicon monomer: the third silicon monomer is (40-55):(40-60):(0.1-5), or even (40-50):(45-59):(0.2-4), in particular (40-48):(50-58):(0.3-3), and preferably (40-45):(52-58):(0.5-2.5).
[0111] Item 11. The silicon polymer material according to any one of the preceding items, further comprising an auxiliary agent, such as selected from initiators, ultraviolet absorbers, blue light absorbers, colorants and diluents, especially the initiator is selected from thermal initiators or photoinitiators.
[0112] Item 12. The silicon polymer material according to any of the preceding items, having one of the following characteristics:
[0113] - moisture content <10%, preferably <3%, most preferably <1%;
[0114] - oxygen permeability>100, preferably>200, most preferably>300;
[0115] - Elastic modulus <5 MPa, preferably <3 MPa, most preferably <1 MPa.
[0116] Item 13. A silicon polymer material according to any of the preceding items, wherein the silicon polymer material comprises antibacterial and lubricating components selected from polyglutamic acid, phosphorylcholine, betaine, polylysine, and polyaspartic acid.
[0117] Item 14. A contact lens made from the silicone polymer material of any one of Items 1 to 13 above.
[0118] Item 15. The contact lens according to Item 14 above, wherein the surface of the contact lens has a surface modification layer, and preferably the surface of the contact lens comprises a covalently cross-linked grafted hydrophilic polymer coating.
[0119] Item 16. A contact lens according to Item 14 or 15, wherein the hydrophilic polymer is selected from one or more of the following: a hydrophilic polymer containing a cyclic amide or cyclic imine structure in the main chain, poly N,N-dimethylacrylamide, polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyethylene oxide, poly 2-ethyl-oxazoline, a polymer containing a phosphorylcholine vinyl monomer, and one or more of a polysaccharide, preferably polyvinyl pyrrolidone, poly N-vinyl-2-piperidone, poly N-vinyl-2-caprolactam, poly N-vinyl-3-methyl-2-caprolactam, poly N-vinyl-3-methyl-2-piperidone, poly N-vinyl-4-methyl-2-piperidone, poly N-vinyl-4-methyl-2-caprolactam, poly N-vinyl-3-ethyl-2-pyrrolidone, poly N-vinyl-4,5-dimethyl-2-pyrrolidone, and polyvinyl imidazole.
[0120] Item 17. A medical device, which is prepared from the silicone polymer material of any one of the aforementioned items 1-13, preferably, it is a contact lens, a colored contact lens, a corneal reshaping lens, a corneal contact lens, an intraocular lens, an artificial cornea, an intracorneal ring, an intracorneal lens, an intraocular filler, a medical device lens or a medical treatment device such as a device for treating ophthalmic diseases, preferably, a low-water-content soft contact lens, which may or may not be equipped with electronic devices.
[0121] Item 18. The medical device according to Item 17, which is a smart contact lens equipped with electronic devices that can be used for monitoring intraocular pressure and / or monitoring eye changes.
[0122] Item 19. A method for preparing a silicon polymer material according to any one of Items 1 to 13, characterized in that it comprises:
[0123] -(1) mixing the required components, such as a first silicon monomer, a second silicon monomer, a third silicon monomer, a crosslinking agent, an initiator or a dye and / or a pigment, a light absorber, and optionally removing bubbles;
[0124] - (2) polymerizing the mixture, optionally placing it in a mold for polymerization, preferably by thermal polymerization and / or photopolymerization; then, optionally, subjecting the obtained polymer to subsequent treatment such as molding.
[0125] Item 20. A method for preparing a contact lens according to any one of Items 14 to 15, characterized in that it comprises the following steps:
[0126] -(1) mixing the required components, such as a first silicon monomer, a second silicon monomer, a third silicon monomer, a crosslinking agent, an initiator or a dye and / or a pigment, a light absorber, and optionally removing bubbles;
[0127] - (2) polymerizing the mixture, optionally placing it into a mold such as a contact lens mold for polymerization, preferably by thermal polymerization and / or photopolymerization;
[0128] -(3) optionally, extracting with an organic solvent;
[0129] - (4) optionally, a hydration step, an equilibration step with a balanced saline solution, and a sterilization step;
[0130] - (5) molding to prepare a substrate;
[0131] -(6) Immersing the substrate in a solution containing an oxidant and a hydrophilic polymer and covalently cross-linking and fixing the substrate.
[0132] Item 21. The method according to Item 20, wherein the oxidant is selected from: one or more of peroxides or persulfides, preferably selected from one or more of hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate.
[0133] Item 22. A method according to Item 20 or 21, wherein the hydrophilic polymer is selected from one or more of the following: a hydrophilic polymer containing a cyclic amide or cyclic imine structure in the main chain, poly N,N-dimethylacrylamide, polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyethylene oxide, poly 2-ethyl-oxazoline, a polymer containing a phosphorylcholine vinyl monomer, and one or more of a polysaccharide, preferably polyvinyl pyrrolidone, poly N-vinyl-2-piperidone, poly N-vinyl-2-caprolactam, poly N-vinyl-3-methyl-2-caprolactam, poly N-vinyl-3-methyl-2-piperidone, poly N-vinyl-4-methyl-2-piperidone, poly N-vinyl-4-methyl-2-caprolactam, poly N-vinyl-3-ethyl-2-pyrrolidone, poly N-vinyl-4,5-dimethyl-2-pyrrolidone, and polyvinyl imidazole. BRIEF DESCRIPTION OF THE DRAWINGS
[0134] Figure 1 The synergistic relationship of the three silicon monomers of the present invention is illustrated. DETAILED DESCRIPTION
[0135] The present invention is further described below in conjunction with specific embodiments. It should be noted that those skilled in the art know that the content of the present invention is not limited by the specific embodiments.
[0136] Examples 1 to 15 Preparation of low water content soft contact lenses
[0137] The low-water-containing soft contact lens is prepared by copolymerizing the silicon-containing monomer, the cross-linking monomer, the initiator, the ultraviolet absorber, the pigment or the dye. All the reagents in the examples can be directly purchased.
[0138] The following abbreviations are used in the examples:
[0139] TRIS: Methacryloyloxypropyl tris(trimethylsiloxy)silane
[0140] PDMS: Bis-3-(meth)acryloxypropyl polydimethylsiloxane
[0141] TMS: Trimethyl(4-vinylphenyl)silane
[0142] EGDMA: Ethylene glycol dimethacrylate
[0143] TMPTMA: Trimethylolpropane trimethacrylate
[0144] D1173: 2-Hydroxy-2-methyl-1-phenyl-1-propanone
[0145] RB19: Reactive Blue 19
[0146] UV416: 2-(4-benzoyl-3-hydroxyphenoxy)ethyl acrylate
[0147] ETOH: Ethanol
[0148] The reaction components and / or diluent (anhydrous ethanol) listed in Table 1 are mixed together and stirred at room temperature for about 20 minutes until all components are dissolved to obtain a reaction preparation. The solution is purged with N2 for about 15 minutes. About 80 microliters of the above reaction preparation are transferred to a clean polypropylene concave half mold, and then covered with a matching polypropylene convex half mold. The half molds are pressed and then irradiated with light (Philips TL03, 50mW / cm 2 , 15 minutes), thereby photopolymerizing to obtain the low water-containing soft contact lens substrates of Examples 1-15.
[0149] The dry contact lens substrate was immersed in a 1% mass concentration KPS aqueous solution for 20 minutes, and then immersed in a 1% mass concentration PVP aqueous solution at 80°C for 20 minutes to make PVP evenly grafted on the surface of the contact lens. Finally, the prepared contact lens was placed in 80°C purified water for hydration for 5 hours to remove the residue. The contact lens was taken out and packaged in a PP cup with a standard saline solution for wet heat sterilization for 30 minutes to obtain the final product.
[0150] Table 1: Reaction components
[0151] Example TRIS PDMS TMS EGDMA TMPTMA D1173 RB19 UV416 ETOH 1 30 60 4 0.1 / 0.4 / 0.5 5 2 32 60 7 / 0.1 0.4 / 0.5 / 3 37 52 10 0.5 / 0.5 / / / 4 40 55 3.5 0.15 0.35 0.1 / / 0.9 5 40 58 1.5 / 0.15 0.3 0.05 / / 6 45 48 0.1 0.05 0.5 0.3 0.05 / 6 7 50 43 6 0.15 0.35 0.5 / / / 8 52 41 5 0.15 / 0.3 0.05 0.5 1 9 55 40 1 0.05 / 0.4 0.05 0.5 3 10 58 41 0.5 / 0.2 0.3 / / / 11 60 37 0.05 / 0.5 0.4 0.05 / 2 12 68 20 8 / 0.5 0.5 / / 3 13 70 27 2.5 / 0.3 0.2 / / / 14 42 57 0.8 0.1 / 0.1 / / / 15 44 53 1.2 / 0.2 0.2 / 0.5 0.9
[0152] Note: The amount of each component in Table 1 is expressed as a percentage by mass of the total mass of each component (100%).
[0153] Comparative Examples 1 to 10 Preparation of Contact Lenses for Comparison
[0154] Referring to the preparation process of Examples 1 to 15, the reaction components and / or diluent (anhydrous ethanol) listed in Table 2 are mixed together and stirred at room temperature for about 20 minutes until all components are dissolved to obtain a reaction preparation. Use N2 to purge the solution for about 15 minutes. Pipette about 80 microliters of the above reaction preparation into a clean polypropylene concave half mold, and then cover it with a matching polypropylene convex half mold. Press the half molds tightly and then irradiate with light (Philips TL03, 50mW / cm 2 , 15 minutes), thereby photopolymerizing to obtain the soft contact lens substrates of Comparative Examples 1 to 10.
[0155] The dry contact lens substrate was immersed in a 1% mass concentration KPS aqueous solution for 20 minutes, and then immersed in a 1% mass concentration PVP aqueous solution at 80°C for 20 minutes to make PVP evenly grafted on the surface of the contact lens. Finally, the prepared contact lens was placed in 80°C purified water for hydration for 5 hours to remove the residue. The contact lens was taken out and packaged in a PP cup with a standard saline solution for wet heat sterilization for 30 minutes to obtain the final product.
[0156] Table 2: Reaction components
[0157] Comparative Example TRIS PDMS TMS EGDMA TMPTMA D1173 RB19 UV416 ETOH 1 49 50 0.01 0.3 0.19 0.5 / / / 2 70 28 / / 0.5 0.5 / / 1 3 34 53 12 0.1 / 0.4 / 0.5 / 4 61 23 15 / 0.5 0.5 / / / 5 70 19 10 0.5 0.5 / / / 6 33 65 1 0.4 0.1 0.5 / / 7 26 65 8 0.5 / 0.5 / / / 8 28 60 5 0.1 / 0.4 / 0.5 6 9 75 23 1.5 0.2 0.3 / / / 10 72 26 1 0.5 0.5 / / /
[0158] Note: The amount of each component in Table 2 is expressed as a percentage by mass of the total mass of each component (100%).
[0159] Test Method
[0160] 1. Moisture content test
[0161] In the present invention, the water content of the medical device (especially contact lens) is tested according to the following method.
[0162] At room temperature, the contact lens sample prepared in the embodiment is placed in a standard phosphate buffer solution for balance overnight, the sample is taken out and blotted dry, and the mass in the hydrated state is recorded with the help of a mass balance, which is calculated as m1. The sample is then dried in an ordinary oven to constant weight, the sample is taken out and placed in a desiccator, and after cooling, it is weighed and the mass is recorded, which is calculated as m2. The moisture content of the sample is calculated according to Formula 1. For detailed methods, see GBT 11417.7-2012 Ophthalmic Optical Contact Lenses Part 7: Physical and Chemical Performance Test Methods, and the test results are listed in Table 3.
[0163]
[0164] 2. Static water contact angle test
[0165] In the present invention, the static water contact angle of the medical device (especially the contact lens) is tested according to the following method. The static water contact angle can reflect the hydrophilicity of the surface of the medical device (especially the contact lens).
[0166] At room temperature, 2 μl of standard saline solution was dropped onto the surface of the contact lens samples prepared in the examples, and the static water contact angles of these samples were tested using a static contact angle tester (model: JGW-360A). The detailed method is shown in GBT 11417.7-2012 Ophthalmic Optical Contact Lenses Part 7: Test Methods for Physical and Chemical Properties, and the test results are listed in Table 3.
[0167] 3. Oxygen permeability test
[0168] In the present invention, the oxygen permeability coefficient of the medical device (especially the contact lens) is tested according to the following method. The contact lens prepared in the embodiment is placed on the oxygen permeability tester, and the oxygen permeability tester adopts the OX-TRAN Model2 / 22H oxygen permeability tester of Mocon Company of the United States. The test temperature is set to the eye temperature (35°C) according to the standard requirements, and the test method is the coulometric method. The detailed method is shown in "GBT 11417.7-2012 Ophthalmic Optical Contact Lenses Part 7: Physical and Chemical Performance Test Methods". The test results are listed in Table 3.
[0169] Elastic modulus test
[0170] In the present invention, the elastic modulus of the medical device (especially the contact lens) is tested according to the following method.
[0171] The contact lens prepared in the example was tested using the testing equipment A1-3000 desktop tensile testing machine and ET-3 electronic thickness gauge. The lens was cut into dumbbell-shaped test pieces (4 mm wide), the cut lenses were placed on the fixture and clamped, and then the tensile testing machine was started for testing. The detailed method is shown in "ASTM D882 Standard Test Method for Tensile Properties of Thin Plastic Sheeting". The measurement was performed with N=8, and the average value of the values of N=6 except the maximum and minimum values was taken as the tensile elastic modulus.
[0172] 5. Elongation at break of lens
[0173] In the present invention, the elongation at break of the medical device (especially contact lens) is tested according to the following method.
[0174] The contact lens prepared in the embodiment was tested using the testing equipment A1-3000 desktop tensile testing machine and ET-3 electronic thickness gauge. The lens was cut into dumbbell-shaped test pieces (4 mm wide), the cut lenses were placed on the fixture and clamped, and then the tensile testing machine was started for testing. The detailed method is shown in "ASTM D882 Standard Test Method for Tensile Properties of Thin Plastic Sheeting". The measurement was performed with N=8, and the average value of the values of N=6 except the maximum and minimum values was taken as the elongation at break.
[0175] 6. Lens transparency
[0176] In the present invention, the transparency of the embodiment lenses is tested according to the following method.
[0177] The contact lens prepared in the example was placed in a D65 standard light source light box with a black bottom sample tray, and the contact lens was observed with the naked eye to evaluate the transparency according to the following criteria. At the same time, another contact lens sample was taken to perform a visible light transmittance τ(λv) test using a Shimadzu UV2600i ultraviolet visible spectrophotometer, with the test band being 380nm-780nm. For detailed methods, see GBT11417.5-2012 Ophthalmic Optical Contact Lenses Part 5: Optical Performance Test Methods.
[0178] A: Excellent lens transparency; τ(λv)≥99%;
[0179] B: The transparency of the lens is slightly worse than A; 90%≤τ(λv)<99%;
[0180] C: The lens is slightly whitish and translucent; 70%≤τ(λv)<90%;
[0181] D: The lens is whitish and opaque; τ(λv)<70%.
[0182] Table 3: Lens performance test results
[0183]
[0184]
[0185] The results show that the contact lenses prepared in Comparative Examples 1 to 10 have poor oxygen permeability, elastic modulus, and transparency compared to those in Examples 1 to 15 of the present invention because the type or ratio of the silicon monomer is not within the scope of the present invention. Specifically, the oxygen permeability of the lenses in Comparative Examples 1, 2, 5, 9, and 10 is poor, and the oxygen permeability is less than 100×10 -11 (cm 2 / s)[mLO2 / (mL.Hgmm)]; the elastic modulus of Comparative Examples 3, 4, 6 and 7 are all poor. The lenses of the first two are hard and brittle, uncomfortable to wear and easy to break; the lenses of the latter two are too soft and inconvenient to operate and wear. The lenses of Comparative Examples 7 and 8 have poor transparency due to insufficient use of the first silicon monomer.
[0186] 7. Performance against protein and lipid adsorption
[0187] 7.1 Anti-protein adsorption performance
[0188] The contact lenses of Example 4, Example 5, Comparative Example 4 and Comparative Example 5 were respectively placed in an aqueous solution containing FITC-labeled bovine serum albumin (0.4 mg / mL) and soaked for 24 hours. Incubate at 37°C in a constant temperature oscillating box at a speed of 100 rpm for 24 hours. Then, the supernatant was taken, the absorbance was measured, and the protein concentration and protein amount adsorbed by the sample were calculated according to the standard curve. The protein detection method was originally quoted from patent CN115028872B (Example 6: Contact lens anti-bovine serum albumin (BSA) adsorption test).
[0189] 7.2 Anti-lipid adsorption performance
[0190] The contact lenses of Example 4, Example 5, Comparative Example 4 and Comparative Example 5 were respectively placed in sample bottles containing 30 mL of triolein solution and immersed at 37° C. for 24 hours. The lenses were then carefully taken out with tweezers and the concentration of triolein in the solution was analyzed.
[0191] The triolein solution was prepared as follows: triolein was dissolved in 8 mass % KOH ethanol solution. A certain amount of triolein was weighed according to a concentration of 6 mg / mL, and 800 mL of 8% KOH ethanol solution was added to dissolve it, and then diluted to 1000 mL with 95% ethanol.
[0192] Table 5: Test results of lens resistance to protein and lipid adsorption
[0193]
[0194] The results show that the material prepared by the silicon monomer combination of the present application has unexpectedly excellent resistance to protein and lipid adsorption than the comparative example material.
[0195] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A silicon polymer material, which is polymerized from silicon monomers, wherein the silicon monomers include at least a first silicon monomer, a second silicon monomer and a third silicon monomer, in, The first silicon monomer is selected from short-chain aliphatic silicon monomers, the second silicon monomer is selected from long-chain polysiloxane monomers, and the third silicon monomer is selected from aromatic silicon monomers. The weight ratio of the first silicon monomer: the second silicon monomer: the third silicon monomer is (30-70): (20-60): (0.05-10).
2. The silicon polymer material according to claim 1, wherein the first silicon monomer is selected from at least one of acrylate or acrylamide silicon monomers, such as a short-chain aliphatic silicon monomer of the following formula: R1=H or C 1-6 Alkyl, preferably H or CH3; n = 1-20, preferably 1-6, even 2-5; R2, R3 and R4 may be the same or different and are selected from one or more of H, CH3, OCH3, OCH2CH3, OSi(CH3)3, CH(OCH2CH3)2 and C(OCH2CH3)3.
3. A silicon polymer material according to any one of the preceding claims, wherein the first silicon monomer is selected from: 3-(trimethoxysilyl)propyl acrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-[dimethoxy(methyl)silyl]propyl methacrylate, 3-[diethoxy(methyl)silyl]propyl methacrylate, 3-(methoxydimethylsilyl)propyl acrylate, 3-(triethoxysilyl)propyl methacrylate, 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, acrylamidopropyltrimethoxysilane, (3-methacrylamidopropyl)triethoxysilane, 3-acrylamidopropyltris(trimethylsiloxy)silane, (3-methacrylamidopropyl)tris(trimethylsiloxy)silane.
4. The silicon polymer material according to any one of the preceding claims, wherein the second silicon monomer is selected from one or more of acryloxy or methacryloxy or acrylamide or methacrylamide mono- or di-terminated polydimethylsiloxanes, such as a long-chain polysiloxane monomer of the following formula: R′1=H or C 1-6 Alkyl, preferably H or CH3; p = 1-20, preferably 1-6, or even 2-5; q = 1-20, preferably 1-6, or even 2-5; m=1-100, preferably 15-60; X is O, S or NH; Y is absent or selected from: O, S, NH, NHCOO(CH2)To, NHCOO(CH2)tS or NHCOO(CH2)tNH, where t=1-20, preferably 1-10, even 2-6, especially 3-5; R'2 and R'3, the same or different, are selected from H or straight or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, either straight chain or C 6-20 One or more of heteroarylalkyl or OCH3 or OCH2CH3 or OSi(CH3)3 or CH(OCH2CH3)2 or C(OCH2CH3)3; R′4 is H or a linear or branched, saturated or unsaturated C 1-20 Alkyl or C 6-20 Arylalkyl, either straight chain or C 6-20 Heteroarylalkyl; preferably C1-4 alkyl; W is X-(CH2)pY(CH2)q.
5. The silicon polymer material according to any one of the preceding claims, wherein the second silicon monomer is selected from the group consisting of: bis-3-(meth)acryloxypropyl polydimethylsiloxane, α-3-(meth)acryloxypropyl-w-n-butyl-polydimethylsiloxane, bis-4-(meth)acryloxybutyl-polydimethylsiloxane, α-4-(meth)acryloxybutyl-w-n-butyl-polydimethylsiloxane, bis-3-(meth)acryloxyethoxypropyl polydimethylsiloxane, α-3-(meth)acryloxyethoxypropyl-w-n-butyl-polydimethylsiloxane Siloxane, bis-4-(meth)acryloxyethoxybutyl polydimethylsiloxane, α-4-(meth)acryloxyethoxybutyl-w-n-butyl-polydimethylsiloxane, bis-3-(meth)acryloxycarbamate propyl polydimethylsiloxane, α-3-(meth)acryloxycarbamate propyl-w-n-butyl-polydimethylsiloxane, bis-4-(meth)acryloxycarbamate butyl polydimethylsiloxane, α-4-(meth)acryloxycarbamate butyl-w-n-butyl-polydimethylsiloxane.
6. The silicon polymer material according to any one of the preceding claims, wherein the third silicon monomer is selected from styryl-containing silicon monomers, such as styryl-containing silicon monomers of the following formula (E): R″1=H or C1-6 alkyl, preferably H or CH3; R"5 and R"6, identical or different, are selected from H or linear or branched, saturated or unsaturated C 1-20 Alkyl, or one or more of Si(CH3)3; X' is absent or is selected from O or S or a linear or branched, saturated or unsaturated C 1-20 Alkyl; or C 6-20 Arylalkyl, or C 6-20 heteroarylalkyl; or C 3-20 heterocyclylalkyl; R″2, R″3 and R″4, which are the same or different, are selected from one or more of CH3, OSi(CH3)3, OSiCH2CH2Si(CH3)3 and SiCH2CH2Si(CH3)3.
7. A silicon polymer material according to any one of the preceding claims, wherein the third silicon monomer is selected from the group consisting of: 4-[tris(trimethylsiloxy)silyl]styrene, 4-[tris(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[tris(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[tris(trimethylsiloxy)silyl]styrene, 4-[methoxybis(trimethylsiloxy)silyl]styrene, 4-[methoxybis(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[tris(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[tris(trimethylsiloxy)silyl]styrene, Styrene, 3-methyl-4-[dimethoxy(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[dimethoxy(trimethylsiloxy)silyl]styrene, 4-[ethoxybis(trimethylsiloxy)silyl]styrene, 4-[ethoxybis(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[ethoxybis(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[ethoxybis(trimethylsiloxy)silyl]styrene, 4-[diethoxy(trimethylsiloxy)silyl]styrene, 4-[diethoxy(trimethylsiloxy)silyl]methylstyrene, 3-methyl-4-[diethoxy(trimethylsiloxy)silyl]styrene, 3,5-dimethyl-4-[diethoxy(trimethylsiloxy)silyl]styrene.
8. A silicon polymer material according to any of the preceding claims, wherein the weight ratio of the first silicon monomer: the second silicon monomer: the third silicon monomer is (40-55): (40-60): (0.1-5), or even (40-50): (45-59): (0.2-4), in particular (40-48): (50-58): (0.3-3), preferably (40-45): (52-58): (0.5-2.5).
9. A medical device, which is prepared from the silicone polymer material of any one of claims 1 to 8, preferably, a contact lens, a colored contact lens, a corneal reshaping lens, a corneal contact lens, an intraocular lens, an artificial cornea, an intracorneal ring, an intracorneal lens, an intraocular filler, a medical device lens or a medical treatment device such as a device for treating ophthalmic diseases, preferably, a low-water-content soft contact lens, which may or may not be equipped with electronic devices.
10. A method for preparing a silicon polymer material according to any one of claims 1 to 8, characterized in that it comprises: -(1) mixing the required components, such as a first silicon monomer, a second silicon monomer, a third silicon monomer, a crosslinking agent, an initiator or a dye and / or a pigment, a light absorber, and optionally removing bubbles; - (2) polymerizing the mixture, optionally placing it in a mold for polymerization, preferably by thermal polymerization and / or photopolymerization; then, optionally, subjecting the obtained polymer to subsequent treatment such as molding.
Citation Information
Patent Citations
Ultra-high dk material
CN112513114A
Silicone hydrogel with high oxygen permeability and corneal contact lens
CN112898506A
Silica hydrogel material
CN116082581A
Method for making embedded hydrogel contact lenses
US20240316886A1
Low water-absorptive ocular lens material, low water-absorptive ocular lens shaped product made thereof, low water-absorptive ocular lens made thereof and process for its production
US5670594A